HIERARCHICAL REGRESSION MODELING TO DETERMINE THE DOMINANT MICRO-MACRO ECONOMIC FACTORS IN THE SHARIA STOCK SECTOR - Aldi Akbar (PT. Jurnal Center Indonesia Publisher, 2026)
The health pandemic several years ago had a significant impact on various sectors, especially companies listed on the Indonesia Stock Exchange. This study was motivated by fluctuations in the price of sharia stocks or the Jakarta Islamic Index (JII) after the Indonesian government officially lifted the pandemic status. By combining macroeconomic and company fundamental factors with hierarchical regression analysis techniques, this study aims to identify which combination of factors influences the return on shares in this sector after the pandemic. The results show that the performance of returns on shares in the sharia sector is dominated by fundamental factors, namely Total Asset Turn Over (TATO) and Return on Assets (ROA). The main finding from this research is that post-pandemic, the performance of the Islamic stock sector is still dominated by corporate fundamental factors, which are efficiency and profitability. The limitation of this research lies in the data range, and it would be very interesting to continue with a longer time period. The technical contribution of this research is that it can provide an overview for investors when deciding to invest, so that they can focus more on corporate fundamental factors first.